Model Of Reliciency Program In Training For Athletes With Minimum National Competition In South Sumatra Woodball Athletes - Hengki Kumbara; Farizal Imansyah; Bambang Hermasnyah (Jurnal Pendidikan Jasmani (JPJ), 2022)
The purpose of this research is to produce a model of resilience program in training for athletes with minimal national competition in South Sumatra woodball athletes. This program model is adapted to the resilience cases experienced by South Sumatra woodball athletes due to the effects of the lack of national competition. This research is a development research (R&D) which refers to the Borg n Gall model. Small-scale trials were carried out on 10 woodball athletes and large-scale trials involved all 24 Pelatda woodball athletes. Collecting data using interviews, value scales, observation sheets. Data analysis techniques using quantitative descriptive analysis. The results of the study are a model of a resilience program in training for athletes with minimal national competition in South Sumatra woodball athletes as outlined in the form of a guidebook. Testing the validity of the program model on large-scale user trials is 0.873 with a reliability above 0.607, namely 0.728 reliable information. The evaluation was carried out on woodball coaching experts and sports psychologists that the resilience program model in training for athletes with minimal national competition in South Sumatra woodball athletes is very feasible to use.